AB0398 Metabolic Morbidities in Patients with Rheumatoid Arthritis: A Cohort Revision. (9th June 2015) - Almeida, T.; Freitas, D.; Monteiro, M.; Carvalheiras, G.; Ferreira, A.; Correia, J.; Vasconcelos, C.
Abstract : Background: Inflammation is a well-known key component in type 2 diabetes, obesity and cardiovascular disease. It is then expected that patients with chronic inflammatory diseases such as Rheumatoid Arthritis (RA) are at increased riskof metabolic syndrome and its components. Objectives: To define the prevalence of metabolic comorbidities (obesity, diabetes mellitus, hypertension, hypercholesterolemia and hypertriglyceridemia) in RA patients and compare it with its prevalence in the general population; determine predictive factors for metabolic morbidities within these patients. Methods: Retrospective study involving patients with definitive 2010 ACR/EULAR criteria for RA, seen at the outpatient clinic of the Clinical Immunology Unit of the Porto Medical Centre between January and June 2013. Charts were reviewed for baseline demographics, metabolic morbidities profile, time from diagnosis and first consultation, past and present treatments and annual erythrocyte sedimentation rate as a measure of disease activity. The prevalence of metabolic morbidities in the RA cohort was compared with the general population based on the adjusted results of large population based studies for the 2001 Census of Portuguese population. Factors associated with metabolic morbidities were determined by logistic regression analysis; factors univariately associated with the metabolic morbidities (p<0.15) were used to construct the models using a stepwise selection method. Results: We analyzed a random sample of 319 patients with definite criteria for RA; 79.3% were females; the mean age was 57.1 years (±12.8); the median time from diagnosis and first consultation were 4.0 years (IQR 12.0) and 3.4 years (IQR 7.0), respectively. The global prevalence of metabolic morbidities was 51.6% for hypercholesterolemia, 45.5% for hypertension, 23.7% for hypertriglyceridemia, 13.9% for obesity and 12.3% for diabetes. We observed a higher adjusted prevalence of diabetes and hypertension in comparison with the general population (p=0.003 and p<0.001, respectively). We observed positive associations between diabetes mellitus and age (p=0.001) and anti-TNF therapy (p=0.007), between obesity and disease duration (p=0.001) and rituximab therapy (p=0.002), hypercholesterolemia and age (p<0.001), male gender (p=0.024), disease duration (p=0.008) and steroid therapy (p=0.047), between hypertriglyceridemia and sulfasalazine therapy (p=0.017) and between hypertension and age (p<0.001). It was observed a negative association between hypercholesterolemia and azathioprine therapy (p=0.032). Conclusions: We found a high prevalence of metabolic morbidities in our cohort of patients with RA and observed an association between treatment options and some of these morbidities, independently of disease activity References: Soeiro AM, Haddad M, Almeida MCF, et al. Rheumatoid arthritis and cardiovascular disease: What is Known about this relationship and what can currently be done for affected patients?. Rev Port cardiol. 2012;31(3):225-232 Gardete-Correia L, Boavida JM, raposo JF. First diabetes prevalence study in Portugal:PREVADIAB study. Diabet Med. 2010 Aug;27(8):879-81 Polόnia J, Martins L, Pinto F. Prevalence, awareness, treatment and control of hypertension and salt intake in Portugal: change over a decade: The PHYSA study. J Hypertens. 2014 Jun;32(6):1211-2 Disclosure of Interest: None declared